Exceptional responders in conservation. Issue 3 (16th January 2018) - Post, Gerald; Geldmann, Jonas
Abstract: Conservation operates within complex systems with incomplete knowledge of the system and the interventions utilized. This frequently results in the inability to find generally applicable methods to alleviate threats to Earth's vanishing wildlife. One approach used in medicine and the social sciences has been to develop a deeper understanding of positive outliers. Where such outliers share similar characteristics, they may be considered exceptional responders. We devised a 4‐step framework for identifying exceptional responders in conservation: identification of the study system, identification of the response structure, identification of the threshold for exceptionalism, and identification of commonalities among outliers. Evaluation of exceptional responders provides additional information that is often ignored in randomized controlled trials and before–after control‐intervention experiments. Interrogating the contextual factors that contribute to an exceptional outcome allow exceptional responders to become valuable pieces of information leading to unexpected discoveries and novel hypotheses. Abstract : Article impact statement : An exceptional‐responder framework may help improve conservation outcomes. Abstract : Respondedores Excepcionales en la Conservación Resumen: La conservación opera dentro de sistemas complejos con conocimientos incompletos sobre el sistema y las intervenciones que se utilizan. Esto resulta frecuentemente en la incapacidad de encontrar métodos aplicables generalizados para aliviar las amenazas que enfrenta la fauna evanescente de la Tierra. Una estrategia que se utiliza en la Medicina y en las ciencias sociales consiste en desarrollar un entendimiento más profundo de los valores atípicos positivos. Dichos valores atípicos pueden ser considerados como respondedores excepcionales cuando comparten características similares. Diseñamos un marco de trabajo de cuatro pasos para identificar a los respondedores excepcionales en la conservación: identificación del sistema de estudio; identificación de la estructura de respuesta; identificación del umbral para lo excepcional; e identificación de las cosas en común entre los valores atípicos. La evaluación de las respondedores excepcionales proporciona información adicional que en muchos casos es ignorada en los ensayos aleatorios controlados y en los experimentos de antes‐después control‐intervención (BACI, en inglés). El cuestionamiento de los factores contextuales que contribuyen a un resultado excepcional permiten que los respondedores excepcionales se conviertan en fragmentos valiosos de información que llevan a descubrimientos inesperados e hipótesis novedosas. 摘要: 保护实践时常在未被完全认知的复杂系统中进行, 而人们对所采取的保护干预知识的掌握也不完备。这经常导致不能找到普适的方法来减轻对地球上正在消失的野生生物的威胁。医学和社会科学中的一种方法被用于深入理解研究中的正异常值。当这些异常值有相似的特性时, 它们可以被看作是异常反应。我们设计了一个四个步骤的体系来识别保护实践中出现的异常反应:研究系统的识别; 反应结构的识别; 异常情况临界值的识别; 以及异常值共性的识别。对异常反应的评估可以为我们提供额外的信息, 而这些信息在随机对照试验和前后控制干预 (BACI) 实验中却常常被忽视。探寻导致异常结果的背景因素可以让异常反应为获得意想不到的发现和新假说提供珍贵的信息。【翻译: 胡怡思;审校: 聂永刚】